2021
DOI: 10.3389/fphar.2021.663776
|View full text |Cite
|
Sign up to set email alerts
|

Icariside II: Anticancer Potential and Molecular Targets in Solid Cancers

Abstract: Icariside II, an active flavonoid, is extracted from the traditional Chinese medicinal herb Epimedii. It possesses multiple biological and pharmacological properties, including anti-inflammatory, anticancer, and anti-osteoporotic properties. In recent years, apoptosis has become the hot spot in anticancer therapies. Icariside II exerts positive effects on inducing apoptosis and inhibiting proliferation in various cancers. The antitumorigenic activity of Icariside II was also proven through cell cycle arrest, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…In addition, the long-term safety of many described drugs is also an area of concern. Therefore, further research to improve the clinical effect of these compounds is warranted ( Xu et al, 2021 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In addition, the long-term safety of many described drugs is also an area of concern. Therefore, further research to improve the clinical effect of these compounds is warranted ( Xu et al, 2021 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Icariside II (ICS), a type of flavonoid, is one of the main active ingredients of the traditional Chinese medicine Epimedium [ 20 ]. Extensive data have shown that ICS could exhibit a variety of biological and pharmacological properties, including anti-inflammatory [ 21 , 22 ], antioxidant [ 23 , 24 ], and anticancer [ 20 , 25 ] activities. Recent studies have also found that ICS has a protective effect against CNS damage.…”
Section: Introductionmentioning
confidence: 99%
“…5 ICS II was proven to have antitumor efficacy by inducing cell-cycle arrest and inhibiting tumor-associated angiogenesis. 6…”
Section: Introductionmentioning
confidence: 99%